(untitled) (Legal journal - Research in Legal and Social Sciences, 2025)
Despite having a robust legal framework for child protection, Paraguay faces persistent structural and generational gaps in the training and performance of legal professionals involved in cases of child sexual abuse and violence (CSAV). The objective of this study is to contribute to the development of more equitable, coordinated, and trauma-informed responses to CSAV by identifying specific gaps to guide effective public policy design. This is a descriptive, qualitative, non-experimental, and cross-sectional investigation conducted between 2023 and 2024 with 1,557 legal professionals across 14 departments, using a validated instrument that measured normative knowledge, access to training, forensic practices, and inter-institutional coordination. The results show that variables such as gender, professional experience, and institutional affiliation significantly influence the quality of the legal response. Women and those with experience in the public sector reported higher levels of training and better practices, whereas men, recent graduates, and those working in the private sector demonstrated lower adherence to protocols. Although 87 % of respondents claimed to have legal knowledge on the subject, only 53 % stated they apply it systematically. Key obstacles identified include a shortage of specialized personnel, weak inter-agency coordination, and the limited use of technical-forensic tools. In conclusion, the findings underscore the urgent need to strengthen institutional capacities and adopt differentiated training policies incorporating children’s rights approach.